Antagonistic Activity of Trichoderma harzianum and Trichoderma koningii Against Colletotrichum sp. Siti Nursyahirah Binti Mohamad Radzip - Siti Nursyahirah Mohamad Radzip (2019)
Trichoderma koningii against Colletotrichum sp. which antrachnose disease has been the cause of decline in chili yield production and concern by the farmer. The aim of this study is to observe whether the both Trichoderma sp. fungi can inhibit the growth of fungus, Colletotrichum sp. within period of time. The experiment carried out by bought chili fruits from Jeli market which has been infected with antrachnose disease. Then the infected part will be cultured and growth on Potato Dextrose Agar (PDA). After that, the pure culture of Colletotrichum sp. need to be subcultured into new PDA for multplying the fungus population. Same goes to the Trichoderma harzianum and Trichoderma koningii need to be subcultured from pure culture into new PDA which provided from laboratory stock. After the three fungus growth, the antagonistic activity of Trichoderma sp. against Colletotrichum sp. can be proceed sp. and Trichoderma koningii, Colletotrichum sp.and Trichoderma harzianum and only Colletotrichum sp. as control in new PDA plate. The data were collected everyday by taking the length of the Colletotrichum sp.growth from backside of plates. The result outcome is as expected where the Trichoderma sp. fungi can inhibit the growth of Colletotrichum sp. with PGI percentage of Trichoderma harzianum is 78% and Trichoderma koningii is 83% against Colletotrichum sp..